Legal Liability Against Marketplace for Promotion of Inappropriate Goods that Harm Consumers - Rizky, Muhammad; Azizi, Fatih Muhammad; Nasution, Mohamad Rizki; Rahman, Alip; Dimyati, Agus (International Journal of Social Service and Research, 2025)
The widespread use of marketplace platforms in online buying and selling activities has brought significant convenience to consumers in Indonesia. However, this phenomenon also presents complex legal challenges, especially related to the circulation of illegal products that are increasingly difficult to monitor. This research examines the legal responsibility of marketplace providers in dealing with the sale of illegal goods based on Law Number 8 of 1999 concerning Consumer Protection (UUPK) and Law Number 11 of 2008 as well as Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE). Using a normative juridical approach and descriptive-analytical method, this research explores how the current regulatory system responds to the issue. The research findings show that although the existing legal framework has provided formal protection, in practice there are still many gaps, especially in the aspects of seller verification, content monitoring, and consumer complaint mechanisms. Marketplaces often play a passive role on the grounds that they are facilitators, even though they have operational control over the system. Therefore, it is necessary to strengthen regulations and increase the active role of platform providers in ensuring the legitimacy of the products being traded. This research also recommends cross-sector collaboration to strengthen supervision and build a safer and more responsible e-commerce ecosystem in 2025 and beyond.